Polymerization in surfactant liquid crystalline phases - Wadekar, M. N.; Pasricha, R.; Gaikwad, A. B.; Kumaraswamy, Guruswamy (Chemistry of Materials, 2005)
We report the formation of cross-linked polysiloxane particles having rodlike and sheetlike morphologies by condensation of monomers in organized liquid crystalline mesophases of nonionic surfactants. The characteristic diffraction pattern obtained from the liquid crystalline surfactant assembly is preserved during polymer synthesis. The polymer colloids are rodlike when synthesized in a hexagonal mesophase and are sheetlike when synthesized in a lamellar mesophase. Interestingly, the size of the polymer particles is on the order of micrometers, viz. 3 orders of magnitude larger than the characteristic size of the surfactant mesophase. Thus, the polymers phase separate from the liquid crystalline phase during polymerization, and organize to resemble the mesophase geometry. The polymer particles are organized so as to minimize the elastic distortion of the surfactant mesophase after they phase separate. We speculate that the observed particle morphologies are formed due to the slow kinetics of polycondensation under our experimental conditions.

Poly(o-toluidine) coatings on copper: electrochemical synthesis from aqueous media - Shinde, V.; Mandale, A. B.; Patil, K. R.; Gaikwad, A. B.; Patil, P. P. (Surface & Coating Technology, 2006)
Poly(o-toluidine) (POT) coatings were synthesized on copper (Cu) by electrochemical polymerization of o-toluidine using aqueous sodium oxalate solution as supporting electrolyte. The resulting coatings were uniform, compact and strongly adherent to the Cu substrate. These coatings were characterized by using cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), X-ray diffraction (XRD) measurements and X-ray photoelectron spectroscopy (XPS). The results of these studies reveal that the sodium oxalate is suitable supporting electrolyte for the electrochemical polymerization of o-toluidine on Cu substrate. It is found that the electrochemical polymerization of o-toluidine takes place after the passivation of the Cu substrate via formation of copper oxalate (CuC2O4, H2O) layer, which is confirmed by XRD and XPS. The optical absorption spectroscopy study reveals the exclusive formation of the pernigraniline base (PB) form of POT. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Conducting polymer coatings; Copper; Corrosion resistant coatings; cyclic voltammetry; poly(o-toluidine) coatings

Poly(o-anisidine) films on mild steel: electrochemical synthesis and biosensor application - Patil, Dewyani; Gaikwad, A. B.; Patil, Pradip (Journal of Physics D-Applied Physics, 2007)
Poly(o-anisidine) (POA) films were synthesized on mild steel from an aqueous oxalic acid solution by electrochemical polymerization of o-anisidine using cyclic voltammetry. These films were characterized by cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). The enzyme glucose oxidase (GOx) was entrapped into the POA film by a physical adsorption method. The resulting POA-GOx films were characterized by UV-visible absorption spectroscopy, FTIR and SEM. The amperometric response of the POA-GOx films was measured as a function of glucose concentration in phosphate buffer solution (pH 7.3). The POA-GOx films exhibited a fast amperometric response (1-5 s) and a linear response in the range of 2-20 mM glucose. The maximum current density and Michaelis-Menten constant of POA/GOx films were found to be similar to 406 mu A cm(-2) and 1.03 mM, respectively. The shelf stability, operational stability and thermal stability of these films were also investigated.

Preparation of nanocrystalline ferroelectric CaBi4Ti4O15 by citrate gel method - Murugan, A. Vadivel; Gaikwad, A. B.; Samuel, V.; Ravi, V. (Ceramics International, 2007)
A gel was formed when an aqueous solution of CaCl2, BiNO3, TiOCl2 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 700 degrees C produced nano crystallites of the ternary oxide, CaBi4Ti4O15 (CBT). The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). The room temperature dielectric constant at 1 kHz is 390. The ferroelectric hysteresis loop parameters of these samples were also studied by a home-built Sawyer-tower circuit. (c) 2006 Elsevier Ltd and Techna Group S.H. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray methods

Preparation of ferroelectric CaBi(4)Ti(4)O(15) powders from novel hydroxide precursors - Deshmukh, Rupali G.; Vaishampayan, Mukta V.; Darshane, Sonali L.; Mulla, Imtiaz S.; Gaikwad, A. B.; Rao, N. Kotaserwara; Ravi, V. (Materials Letters, 2008)
Ferroelectric CaBi(4)Ti(4)O(15) (CBT) powders were prepared for the first time from their respective hydroxides. Commercially purchased Ca(OH)(2) is mixed thoroughly with freshly prepared Bi(OH)(3) and Ti(OH)(4) in stoichiometrie ratio and heated at different temperatures ranging from 100 to 600 degrees C. The CBT phase found to be formed at 500 degrees C by the X-ray diffraction studies. This is the lowest temperature so far reported in the literature for the formation of CBT phase. The advantage of this method is that it also avoids the formation of calcium carbonate phase during synthesis. The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD) method. The average particle size and morphology were studied by scanning electron microscopy (SEM) technique. (c) 2007 Elsevier B.V All rights reserved.
Keywords: CaBi(4)Ti(4)O(15); Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray methods

Poly(o-anisidine) coatings on brass: synthesis, characterization and corrosion protection - Chaudhari, Sudeshna; Gaikwad, A. B.; Patil, P. P. (Current Applied Physics, 2009)
Poly(o-anisidine) (POA) coatings were synthesized on brass by electrochemical polymerization of o-anisidine in aqueous salicylate solution by using cyclic voltammetry. These coatings were characterized by cyclic voltammetry, UV-visible absorption spectroscopy., Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). The corrosion protection aspects of POA coatings on brass in aqueous 3% NaCl solution were investigated by potentiodynamic polarization technique and electrochemical impedance spectroscopy (EIS). The potentiodynamic polarization measurements show that the POA coating has ability to protect the brass against corrosion. The corrosion potential was about 0.204 V versus SCE more positive for the POA coated brass than that of uncoated brass and reduces the corrosion rate of brass almost by a factor of 800. The corrosion behavior of the POA coatings was also investigated by EIS through immersion tests performed In aqueous 3% NaCl solution. The evolution of the impedance parameters with the immersion time was studied and the results Show that the POA acts as a protective coating on brass against corrosion in 3% NaCl solution. The water uptake and delamination area were also determined to further support the corrosion protection performance of the POA coating. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: brass; conducting polymers; Corrosion resistant coatings; cyclic voltammetry; Electrochemical impedance spectroscopy; Electrochemical polymerization; poly(o-anisidine)

Preparation and characterization of silver particulate films on softened polystyrene and poly(4-vinylpyridine) blends - Gurumurthy, S. C.; Pattabi, Manjunatha; Krishna, Shreedhar; Gaikwad, A. B. (Journal of Materials Science-Materials In Electronics, 2014)
Results of the investigations carried out on the optical properties of silver particulate films deposited at a rate of 0.4 nm/s on softened polystyrene and poly(4-vinylpyridine) (P4VP) blends held at 455 K are reported. Under the conditions of deposition, a sub-surface particulate structure is expected. It had been shown earlier that the morphology of the sub-surface particulate structure is dependent on polymer-metal interaction. In the present studies, an inert polymer like polystyrene (PS) is blended with an interacting polymer P4VP. The optical studies on the silver particulate films deposited on softened blends of PS/P4VP have been carried out. The results show a shift in plasmon resonance to higher wavelength with increasing P4VP concentration of the blends in comparison to that of the films deposited on pure PS. An X-ray photoelectron spectroscopy study at two different electron take off angles indicates the formation of subsurface particulate structures for films deposited on blends.